2010
DOI: 10.1177/1468796810372297
|View full text |Cite
|
Sign up to set email alerts
|

Whiteness in the glare of war: Soldiers, migrants and citizenship

Abstract: The figure of the soldier-migrant demonstrates why it is important to bring the question of military service into contemporary sociological debates about citizenship, belonging and racism. The article draws on an understanding of whiteness as a fundamental component of historical and gendered notions of citizenship that feed the ‘hypnotic ideals’ of national identity. Because of academic specialism and disciplinary boundaries, however, the intersections between civil and military spheres are often neglected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Previous studies suggest that an individual's level of globalism, lack of active local ties, as well as higher levels of consumerism significantly increase the tendency to evade military service (Adres et al 2012: 95). Changes in citizenship alter the idea of conscription as an obligatory part of citizenship (Eichler 2013;Ware 2010).…”
Section: Evading Military Servicementioning
confidence: 99%
“…Previous studies suggest that an individual's level of globalism, lack of active local ties, as well as higher levels of consumerism significantly increase the tendency to evade military service (Adres et al 2012: 95). Changes in citizenship alter the idea of conscription as an obligatory part of citizenship (Eichler 2013;Ware 2010).…”
Section: Evading Military Servicementioning
confidence: 99%
“…Ministry of Defence October 2012. 9 The rapid increase in numbers of 'military migrants' soon proved its PR value in the face of British National Party claims that military service in defence of the UK was an all-white affair (Ware 2010). However, the arrest in 2017 of five servicemen allegedly discovered to be members of the banned neo-Nazi organization National Action indicated that current and former soldiers could be particularly vulnerable to the allure of white supremacist groups (Davey 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Military history -whether deeds of past glory or simply the re-iteration that 'We Were There Too' -acquires value as a resource for survivors and descendants, whether it is made to re-articulate group identities or provide the basis of assimilation and integration strategies (Krebs 2004). In the UK and elsewhere in Europe, a combination of factors has re-animated discussions about the significance of military service -and specifically death in uniform -for grounding citizenship claims for postcolonial migrants and their descendants (Qureshi 2013, Ware 2010). Yet as Nirmal Puwar writes in an essay on the 'Spatial Interruptions of War, Nation, and Memory', while these kinds of gestures aspire to bring in those who have been hitherto excluded, 'they are largely limited by the fact that the categories that pervade our existing notions of the nation and the national archives remain largely unquestioned' (2011, pp.…”
Section: Theatrics Of Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned gender research is important, yet, with the exception of Barker (2009), Ware (2010), Eichler (2014) and Chisholm (2014aChisholm ( , 2014bChisholm ( , 2015, has not yet systematically engaged with discussions of how global security labour chains constitute and are constituted by gendered and racialised relations. Such a gap results in missing the ways global South labourers and their communities are called upon to support the industry through paid and unpaid work.…”
Section: Introductionmentioning
confidence: 99%